A low-cost predictive display for teleoperation: Investigating effects on human performance and workload. Issue 145 (January 2021) - Dybvik, Henrikke; Løland, Martin; Gerstenberg, Achim; Slåttsveen, Kristoffer Bjørnerud; Steinert, Martin
Highlights: A simple predictive display for teleoperation application was developed. An experiment with N = 57 participants tested the predictive display. There was a 20% increase in human performance with the aid of the predictive display. Regular gamers performed 30% better with the predictive display. An exploratory data analysis (EDA) investigated confounding factors with confirmatory results. Abstract: Teleoperation in an environment with latency is difficult and highly stressful for human operators, resulting in high cognitive workload and decreased human performance. This work investigates if a simple predictive display can increase performance and lower subjective workload for the human operator when teleoperating a remotely operated vehicle (ROV). A predictive display based on image transformation was developed by applying positional and scale transformations to the video feed and tested. An experiment was designed, consisting of a simple navigational task (peg-in-hole game) with a ground ROV, in three distinct conditions: C1. Latency, C2. Latency with predictive display (PD) and C3. Baseline (no added latency). Findings from N = 57 participants show a statistically significant increase of 20% in human performance with the aid of the predictive display. Although differences in subjective workload was not statistically significant, both subjective performance and actual game performance did increase significantly by using the predictive display. In fact, the latter almost doubled for participants defining themselves as regular gamers. Lastly, A principle component analysis (PCA) was conducted investigating confounding factors with confirmatory results.